1999
DOI: 10.1016/s0925-4773(99)00112-4
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of transforming growth factor-β type II receptor signaling accelerates tooth formation in mouse first branchial arch explants

Abstract: Members of the transforming growth factor-beta (TGF-beta) superfamily signal through their cognate receptors to determine cell phenotypes during embryogenesis. Our previous studies on the regulation of first branchial arch morphogenesis have identified critical components of a hierarchy of different TGF-beta isoforms and their possible functions in regulating tooth and cartilage formation during mandibular morphogenesis. Here we tested the hypothesis that TGF-beta type II receptor (TGF-beta IIR) is a critical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 38 publications
0
47
0
1
Order By: Relevance
“…Immunostaining was completed by following standard procedures (Chai et al, 1999;Hosokawa et al, 2005). Briefly, serial sections (6 m) of cultured palates transfected with control or Smad2 siRNA were cut and mounted onto the same slide to ensure exposure to the same antibody concentration.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Immunostaining was completed by following standard procedures (Chai et al, 1999;Hosokawa et al, 2005). Briefly, serial sections (6 m) of cultured palates transfected with control or Smad2 siRNA were cut and mounted onto the same slide to ensure exposure to the same antibody concentration.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…TGF-␤ and its cognate receptors are important regulators during mandibular morphogenesis (Pelton et al, 1990;Chai et al, 1994Chai et al, , 1999. Targeted disruption of TGF-␤ signaling (such as TGF-␤2 null mutant) results in multiple developmental defects, including a small mandible with its angle missing.…”
Section: Discussionmentioning
confidence: 99%
“…This AdSmad7 has been used successfully to block the phosphorylation of Smad2 upon TGF-␤ stimulation in various studies, demonstrating its effectiveness as a negative TGF-␤ signaling regulator (Nakao et al, 1999;Zhao et al, 2000). Our previous study has shown that adenoviral vectors are very effective in altering TGF-␤ type II receptor gene expression in cultured mandibular explants (Chai et al, 1999).…”
Section: Meckel's Cartilage Development Is Sensitive To the Expressiomentioning
confidence: 97%
See 2 more Smart Citations